Mathematical model structures of supply chain optimisation studies and an innovative approach proposal. (7th November 2021) - Yildirim, Mustafa; Yenisey, Mehmet Mutlu
Supply chain optimisation has been the subject of many scientific studies due to its mathematical structure. In this study, some optimisation studies that consider the components of the supply chain for modelling and to help to make decisions for supply chain management problems are examined. These studies in the literature have been classified in terms of mathematical model structures. Optimisation of supply chain problems and complexity of problems are mentioned. For the optimisation of the supply chain, a new innovative approach has been proposed by using the succession relationship between the components of the supply chain. In accordance with the proposed approach, a solution method has been described and its results are shown on a sample problem. It is aimed that the proposed method will bring a new approach suitable for solving complex problems, especially supply chain optimisation problems, and contribute to finding better solutions. Development opportunities are evaluated by examining the results.